Novelty of Bioengineered Iron Nanoparticles in Nanocoated Surgical Cotton: A Green Chemistry - Bhavika Turakhia; Saujanya Chikkala; Sejal Shah (Advances in Pharmacological Sciences)
The current focus of nanotechnology is to develop environmentally safe methodologies for the formulation of nanoparticles. The phytochemistry of Zingiber officinale inspired us to utilize it for the synthesis of iron nanoparticles. GC-MS analysis revealed the phytochemical profile of ginger. Out of 20 different chemicals, gingerol was found to be the most potent phytochemical with a retention time of 40.48 min. The present study reports a rapid synthesis method for the formation of iron nanoparticles and its potential efficacy as an antibacterial agent and an antioxidant. Because of its antibacterial property, ginger extract was used to coat surgical cotton. Synthesized ginger root iron nanoparticles (GR-FeNPs) were characterized by UV-visible spectroscopy, Fourier-transform infrared spectroscopy (FT-IR), X-ray diffraction analysis, and particle size analysis. XRD confirmed the crystalline structure of iron oxide nanoparticles as it showed the crystal plane (2 2 0), (3 1 1), (2 2 2), and (4 0 0). The particle size analyzer (PSA) showed the average size of the particles, 56.2 nm. The antimicrobial activity of the FeNPs was tested against different Gram-positive and Gram-negative bacteria. E. coli showed maximum inhibition as compared with the other organisms. Antioxidant activity proved the maximum rate of free radicals at 160 µg/mL produced by nanoparticles. In addition, the antimicrobial activity of nanocoated surgical cotton was evaluated on the first day and 30th day after coating, which clearly showed excellent growth inhibition of organisms, setting a new path in the field of medical microbiology. Hence, iron-nanocoated surgical cotton synthesized using green chemistry, which is antimicrobial and cost effective, might be economically helpful and provide insights to the medical field, replacing conventional wound healing treatments, for better prognosis.